A Competence Comparison of Learning Results Using Problem Based Learning With Discovery Learning on Integrated Themat Learning in Class IV Basic School - Elmita Waslina; Farida F; Yanti Fitria; Mudjiran Mudjiran (International Journal of Educational Dynamics, 2019)
This study aims to compare the application of Problem Based Learning learning models to Discovery Learning students in grade IV SD 187 Pekanbaru. This research was conducted with experimental research methods with a comparative approach. "This type of research is the same as post-facto research, ie data is collected after all phenomena or events under investigation take place or about things that happen so that nothing is controlled. the average value of the pretest and posttest of student learning outcomes using the proble based learning model that is equal to 63,676 and 83,382, higher than the results of learning the pretest and posttest students using discovery learning methods, which amounted to 40,454 and 70,606. Thus, the Test Result shows Fcount is greater than Ftable, which is 10.176> 3.98856, so Ho is rejected and Hi is accepted, meaning that it can be concluded that there is an interaction between the problem based learning model and the discovry learning model on student learning outcomes.